TRADITIONAL AND INNOVATIVE TOOLS OF ANTI-CRISIS MANAGEMENT OF AGRO-INDUSTRIAL ENTERPRISES (INNOVATIVE ECONOMY, 2021)
Voloshchuk K.B., Ivanyshyn O.V., Savchuk O.V. TRADITIONAL AND INNOVATIVE TOOLS OF ANTI-CRISIS MANAGEMENT OF AGRO-INDUSTRIAL ENTERPRISESPurpose. The aim of the study is improving traditional and the need to use innovative tools for crisis management of agro-industrial enterprises.Methodology of research. General scientific and special methods were used in the course of the research, namely: dialectical methods in the identification of crisis phenomena; statistical methods (averages and relative values, indices for estimating the obtained actual values of indicators and comparing them in the dynamics); analysis and synthesis - to substantiate trends in the development of different categories of farms and net profits of enterprises, graphic - in the formation of conceptual foundations of crisis management of enterprises, etc.Findings. Trends in production are revealed as unstable, due to significant fluctuations in the direction of reducing production indices of enterprises and in all categories of farms. It was found that the share of profitable enterprises as a whole decreased and the share of unprofitable agro-industrial enterprises increased.The use of a wide range of traditional anti-crisis tools by modern management in diagnosing signs and determining the probability of crisis phenomena in enterprises, stabilization of the situation, development and implementation of programs to overcome the crisis, is proved. The directions of improvement of traditional anti-crisis management tools based on the use of digital technologies (PLM-systems, ERP-systems, CALS, CRM and Big Data), etc. are revealed.It is proposed to apply innovative tools, such as benchmarking; reengineering; outsourcing; risk management; express diagnostics; TEI-examinations, anti-crisis PR-management; interactive, simulation and structural-cognitive modelling; to carry out intellectualization of administrative processes for substantiation of alternatives of strategic management for the purpose of maintenance of steady effective development of the enterprises.Theoretical developments and generalizations of scientific approaches and practices of crisis management allowed to build a conceptual block diagram of crisis management, which combines the main components of new business models, which will facilitate the transition to better methods of business, will facilitate rapid substantiation of new high-quality timely decisions, the correct selection of innovations taking into account the peculiarities of business and dynamic changes in the environment of enterprises.Originality. A conceptual block diagram of anti-crisis management is proposed, which combines the use of the main components of traditional and innovative tools for choosing strategic directions for sustainable development of agro-industrial enterprises.Practical value. The obtained research results will contribute to the formation of an effective system for improving anti-crisis instruments, models of business process administration and productivity of enterprises.The use of tools for selecting optimal measures will increase the level of crisis resilience of enterprises and timely adaptation to dynamic changes in the external and internal environment to create favourable conditions and effective sustainable development.Key words: anti-crisis management, innovative tools, benchmarking, reengineering, outsourcing, risk management, express diagnostics, TEI expertise, urgent actions, digital and IT technologies.
Keywords: Key words; anti-crisis management; innovative tools; benchmarking; reengineering; outsourcing; risk management; express diagnostics; TEI expertise; urgent actions; digital and IT technologies.